Les réseaux des académies et des écoles d’art en Europe méridionale (1740-1820) : projet et perspectives de recherche - Émilie Roffidal (Les Cahiers de Framespa)
The present contribution wants to report a research project initiated within FRAMESPA, on Academies and schools of art in Southern Europe. Beyond their hybrid character, these institutions have in common the same founding intention which opens the way to a wide study on this new phenomenon of creation and development of artistic training centers since 1740s. The questioning of several circulation markers (artists' mobilities, sendings of works, sociability, correspondences) has to informed on the density of their links and the interactions with intellectual and economic networks. This study intends to specify the roles of these institutions in the transmission of knowledges and in the dissamination of a «good taste» that must soak manufactured goods and, in this way, participate to a better prehension of the cultural and economic history of Europe around 1800.